BIM, Digital Twins, IoT and AI for Post-Construction Hospital Built Environment Management: A Systematic Scoping Review - Virginia Adele Tiburcio (Green Health, 2026)
Healthcare facilities represent some of the most operationally complex and critical built environments, in which building performance directly influences patient safety, clinical outcomes, staff wellbeing and management efficiency. The progressive digitisation of the construction and Facility Management (FM) sectors, driven by Building Information Modelling (BIM), Digital Twin (DT), the Internet of Things (IoT) and Artificial Intelligence (AI), offers transformative potential for the management of hospital infrastructure, predictive maintenance and indoor environmental monitoring. Despite a growing body of scientific literature, existing systematic reviews focus predominantly on clinical or patient-facing Digital Twin applications, leaving the built environment perspective—encompassing architectural systems, technical infrastructure and post-construction lifecycle management—largely unexplored. This Systematic Scoping Review follows the PRISMA-ScR protocol. A structured database search on Scopus yielded 194 records; after title/abstract screening and full-text review, the final corpus, defined here as the final set of included studies, comprises 166 studies (2013–2026; 2026 partial through 21 April) coded through a multidimensional thematic matrix. Results reveal a marked acceleration in publications from 2023 onwards, with BIM (56.6%) and Digital Twin (46.4%) as the dominant technologies and Facility Management as the prevailing domain (69.3%). The principal finding concerns implementation maturity: 52.4% of studies remain at a conceptual level, 38.6% are Prototype/Proof-of-Concept and 9.0% are Pilot/Testbed; no study documents a fully operational hospital deployment. Identified gaps include limited system interoperability, the absence of explicit normative references and insufficient integration of environmental sustainability. Beyond technical and sustainability dimensions, the review highlights a critical gap in the explicit linkage between built environment management and direct health outcomes for occupants: real-time digital monitoring of indoor environmental quality (IEQ) parameters remains the least operationally implemented domain (9.6% of studies), despite its documented effects on patient recovery, infection control and healthcare staff performance.